2010
DOI: 10.1002/adem.200980078
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Gallium Releasing 3‐D Alginate Coated 45S5 Bioglass® Based Scaffolds for Bone Tissue Engineering

Abstract: The aim of this work was to develop functional three‐dimensional scaffolds based on Bioglass® derived glass–ceramics for bone tissue engineering (TE) with prophylaxis effect against infections. The highly porous scaffolds were fabricated by the foam replication technique and then coated with sodium alginate crosslinked with Ga3+. It was confirmed that the polymer coating did not affect the interconnectivity of the scaffold pore structure. The resulting composite scaffold exhibited antibacterial effect and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 68 publications
4
45
1
Order By: Relevance
“…This observation was the same reported in the previous study of Mouriño et al, 46 who found that the surface of Bioglass-based scaffolds similar to the ones used in this study became rougher after coating with a second layer of alginate. 46 This effect is probably caused by polymer agglomeration during drying. In detail, the alginate coating, for example, took longer time to be dried compared to the PDLLA/P123 coating and thus this differential shrinkage is likely responsible for the generation of a marked surface rugosity.…”
Section: -4 Nooeaidsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation was the same reported in the previous study of Mouriño et al, 46 who found that the surface of Bioglass-based scaffolds similar to the ones used in this study became rougher after coating with a second layer of alginate. 46 This effect is probably caused by polymer agglomeration during drying. In detail, the alginate coating, for example, took longer time to be dried compared to the PDLLA/P123 coating and thus this differential shrinkage is likely responsible for the generation of a marked surface rugosity.…”
Section: -4 Nooeaidsupporting
confidence: 92%
“…3(A)]. This observation was the same reported in the previous study of Mouriño et al, 46 who found that the surface of Bioglass-based scaffolds similar to the ones used in this study became rougher after coating with a second layer of alginate. 46 This effect is probably caused by polymer agglomeration during drying.…”
Section: -4 Nooeaidsupporting
confidence: 90%
“…It is believed that bioglasses doped with ions such as Ga 3? and Zn 2? offer antibacterial, anti-inflammatory, anti-tumor and immunosuppressive properties [52][53][54]. In addition, Ga increases the Lewis acidic strength of bioglass, which makes them suitable for interaction with biomolecules such as proteins and drugs [37].…”
Section: Indirect Immunostainingmentioning
confidence: 99%
“…Hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) shows IR absorption due to vibrations of phosphate and hydroxyl groups. According to the literature [64][65][66][67], an overview of all peaks identified for the different coatings is given in Table 3. As shown in Fig.…”
Section: In Vitro Assessment In Sbf Solutionmentioning
confidence: 99%